2022
DOI: 10.3389/fonc.2021.785022
|View full text |Cite
|
Sign up to set email alerts
|

One Cycle of Concurrent Chemotherapy vs. Two Cycles of Concurrent Chemotherapy With Radiation Therapy in Patients With Limited-Stage Small Cell Lung Cancer

Abstract: BackgroundThe optimal number of concurrent chemotherapy cycles during thoracic radiotherapy (RT) in patients with limited stage-small cell lung cancer (LS-SCLC) is not well defined. The purpose of this study was to evaluate the impact of the number of concurrent chemotherapy cycles on prognosis of LS-SCLC.Material and MethodsPatients with LS-SCLC treated with concurrent chemo-radiotherapy from May 2008 to December 2020 in our hospital were retrospectively analyzed. The prescribed radiation dose was 60Gy admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…SCLCs are highly aggressive and malignant which lead to poor prognosis and hard to predict prognosis, even in LS-SCLC. Our research group has conducted numerous studies on the timing of radiotherapy [ 24 ], the target area of radiotherapy [ 25 , 26 ], radiotherapy techniques [ 27 ], treatment sequencing [ 28 ] and the number of cycles of chemotherapy [ 29 ] during chemoradiotherapy, as well as prophylactic cranial irradiation(PCI) [ 30 ] for SCLC. Our findings reveal the difficulty in accurately predicting the prognosis of LS-SCLC from a purely clinical standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…SCLCs are highly aggressive and malignant which lead to poor prognosis and hard to predict prognosis, even in LS-SCLC. Our research group has conducted numerous studies on the timing of radiotherapy [ 24 ], the target area of radiotherapy [ 25 , 26 ], radiotherapy techniques [ 27 ], treatment sequencing [ 28 ] and the number of cycles of chemotherapy [ 29 ] during chemoradiotherapy, as well as prophylactic cranial irradiation(PCI) [ 30 ] for SCLC. Our findings reveal the difficulty in accurately predicting the prognosis of LS-SCLC from a purely clinical standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…SCLC is highly sensitive to radiotherapy in the early stages of treatment, but radioresistance inevitably develops in a significant proportion of patients [ 32 , 33 ]. Cancer radioresistance is an intricate phenomenon that has attracted a lot of attention, and there are two main hypotheses to explain it [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge remains how many cycles of IC gives the best outcome. Yu et al [ 14 ] compared 1 versus 2 cycles of concurrent chemo-radiotherapy in 370 patients with limited stage NSCLC and concluded that 2 cycles of concurrent chemotherapy during RT were not necessarily superior compared to 1 cycle. Chen et al [ 15 ] meanwhile assessed the association between the number of cycles of IC, and radiation therapy dose with overall survival in 227 unresectable stage III NSCLC patients, and concluded that number of cycles of IC did not interfere with survival, but 3 or more cycles induced more grade 3 to 4 hematological toxicities.…”
Section: Introductionmentioning
confidence: 99%